Nutritional value of silage Erythrina glauca forage with different levels of molasses and rice flour (Revista Sistemas de Producción Agroecológicos, 2010)
This investigation evaluated the silage of Erythrina glauca forage in its nutritional quality, to be used later on in the animal feeding of in Colombia. The Erythrina glauca silage, was pack in silage bag was added to forage three levels of molasses (10%, 15% and 20%), besides, was added 3% of flour of rice by treatment, being the other half of the forage without flour, the silaje, was analyzed in four times of maturation: 0, 30, 60 y 90 days; with three repetitions each one. The trial was randomized completely to the chance with a factorial arrangement of 3x4x2, being respectively for treatments, and times of maduration and addition of flour of rice: It was used variance analysis and test of Tukey. The evaluated variables were: Dry matter, protein, raw fiber, fat, non-nitrogenaus extract, ash, the fiber in the neuter detergent (NFD), fiber in the acid detergent (AFD) and degradation in the rumen of the dry matter (DDM). The content of matter of the silage increased (P0.05) on the DM content. The protein content decreased (P
Keywords: Erythrina glauca; silage; nutritional quality